Development and validation of an evidence based educational program for adults undergoing anterior cruciate ligament reconstruction surgery in the United Arab Emirates - Alzaabi, Hana (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScPhysio (Physiotherapy))--University of Stellenbosch, 2010.